Environmental inorganic chemistry for engineers - Speight, James G. (Butterworth-Heinemann is an imprint of Elsevier, 2017)
This explains the principles of inorganic contaminant behavior, also applying these principles to explore available remediation technologies, and providing the design, operation, and advantages or disadvantages of the various remediation technologies.
Obsahuje index.
Keywords: environmentální chemie; anorganická chemie; environmental chemistry; inorganic chemistry; monografie; elektronické knihy; monographs; electronic books